Who’s for dinner? Bird prey diversity and choice in the great evening bat, Ia io - Gong, Lixin; Shi, Biye; Wu, Hui; Feng, Jiang; Jiang, Tinglei (Ecology and evolution, 2021)
The mysterious predator–prey interaction between bats and nocturnally migrating birds is a very rare and incredible process in natural ecosystems. So far only three avivorous bat species, including two noctule bats (Nyctalus lasiopterus and Nyctalus aviator) and the great evening bat (Ia io), are known to regularly prey on songbirds during nocturnal avian migration. The information related to the diversity and the characteristics of the birds as prey and the hunting strategy in both species of noctule bats are already clear. However, the diversity of bird prey in the diet of I. io as confirmed by molecular identification remains unknown. Moreover, like hunting insects, it remains unclear whether the avivorous bats opportunistically prey on birds. Here, we used DNA metabarcoding to investigate the bird prey composition, diversity, and choice in diets of I. io. We found I. io consumed 22 species of seven families from Passeriformes with a body mass of 6–19 g, and preferentially selected small‐sized passerine birds for optimizing the benefit/risk trade‐off. Moreover, most of the species preyed upon were migratory birds, while four species were local resident birds, indicating that I. io may adopt both aerial‐hawking and gleaning strategies on songbirds as do the other two noctules. Further, I. io body mass did not influence in prey choice and predation richness on birds, suggesting I. io is an opportunistic avivorous predator. This study provides novel insights into the avian dietary ecology of I. io and completes the analysis of predator/prey interaction between three avivorous bats and nocturnally migrating birds. Our results also indicate bat predation on birds which occurs as an act of ecological opportunity may subject bats to intense natural selection pressure, causing them access to the new diet‐defined adaptive zones. We used DNA metabarcoding to investigate the bird prey composition, diversity, and choice in diets of the avivorous bat, Ia io. We found I. io consumed 22 species of seven families from Passeriformes. Moreover, I. io may adopt both aerial‐hawking and gleaning strategies on songbirds as do the other two noctules. Ia io body mass did not influence in prey choice and predation richness on birds, suggesting I. io is an opportunistic avivorous predator. Our work provides novel insights into the avian dietary ecology of I. io and completes the analysis of predator/prey interaction between three avivorous bats and nocturnally migrating birds.